THE GEOCHEMICAL VARIATIONS OF MID-CRETACEOUS LAVAS ACROSS WESTERN SHANDONG PROVINCE, CHINA AND THEIR TECTONIC IMPLICATIONS - Ying J.; Zhou X.; Zhang H. (My University, 2006)
Major and trace element as well as Sr–Nd isotopic compositions of mid-Cretaceous lavas across western Shandong Province, China have been studied. These lavas can be generally divided into southern Shandong group (including Pingyi and Mengyin) and northern Shandong group (including Laiwu and Zouping) based on their geochemistry. The southern group lavas are characterized by extreme enrichment in LREE, large ion lithophile elements (LILE), and depletion in HFSE along with EMII-like Sr–Nd isotopic compositions, suggesting that the crustal involvements play a significant role in their petrogenesis. Comparing studies with Fangcheng basalts reveal that the Triassic continent–continent collision between the Yangtze craton (YC) and the North China craton (NCC), and subsequent extensive modification of the sub-continental lithospheric mantle (SCLM) beneath the south part of the NCC by silicic melts released from the subducted Yangtze lower crust, formed an enriched lithospheric mantle which was the source of the southern Shandong group lavas. In contrast, the northern Shandong group lavas are mildly enriched in LREE and LILE relative to those of the southern group lavas. The isotope compositions are also distinctive in that the Sr isotopic ratios are very low. Available geochemical evidence and comparing studies with spatially closed related mafic intrusions suggest that the SCLM feeding the northern group lavas seems to be linked to carbonatitic metasomatism and changed modal proportion of phlogopite and clinopyroxene in the mantle rather than subduction-related modifications. The contrasting geochemical characters of the mid-Cretaceous lavas across western Shangdong suggest that the SCLM of the NCC is spatially heterogeneous in Mesozoic.
Keywords: CHINA; SHANDONG PROVINCE; GEOCHEMISTRY; MID-CRETACEOUS; LAVAS; Cretaceous; Triassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Triassic; Мезозой::Триасовая